Polyoxometalate catalysts for the synthesis of N-heterocycles - Qilong Hu; Ke Li; Xuejiao Chen; Yufeng Liu; Guoping Yang (Polyoxometalates, 2024)
N-Heterocycle compounds are crucial scaffolds in natural products, synthetic molecules, agricultural chemicals, and pharmaceuticals. Hence, green catalytic systems for the synthesis of N-heterocycles have been widely researched in organic synthesis and industrial catalysis. Polyoxometalates (POMs) are polynuclear metal–oxygen clusters with diverse structures and physicochemical properties. POMs exhibit multiple advantageous properties such as adjustable acidity, redox properties, high thermal stability, and nontoxic nature. Therefore, POMs have been widely investigated for their application in N-heterocycles synthesis and held great potential for industrial applications. In this review, we summarize recent advances (mainly from 2010 to 2023) in the synthesis of N-heterocycles, such as pyrroles, indoles, pyridines, and benzodiazepines, catalyzed by heteropolyacids (HPAs), modified HPA catalysts, and transition metal-modified POMs. The prospects of POM-based catalytic systems for the synthesis of N-heterocycles are also outlined.